Implementation of Child-Friendly District Policy in Lampung Utara District - Andi Wijaya; Iqbal Miftakhul Mujtahid; Mani Festati Broto (Budapest International Research and Critics University, 2022)
Policy Implementation (KLA) in North Lampung Regencyis a political and constitutional necessity of the Regional Government in the context of fulfilling children's rights and special protection for children, the problem is that there is a gap between policy objectives and the realization of policy performance targets. To be able to achieve its objectives, a policy requires effectiveness prerequisites for which an analysis of the effectiveness of the KLA policy is carried out and the determinants/factors that support and hinder itimplementation of the KLA policy.The research method used is researchqualitative descriptive, using public policy theory Matland, (1995) and other relevant theories. ProcessData collection was carried out by in-depth interviews with research informants, observation and documentation, while the stages of the processing/analysis process were editing data, presenting data and interpreting data. The results of the study concluded that the implementation of the KLA policy in North Lampung Regency has not been fully effective, it can be seen from the results of the research KLA policy as a child-based development system has not been able to fully transform KHA, integrate the commitment of Government and non-Government resources in a comprehensive and sustainable way. The strategic recommendation in the research is for policy authorities to1) optimize the integration of Government and non-Government commitments and resources, 2) carry outreviewlocal government policies/regulations, 3) carry out communication, socializationand policy publications, 4) implement community empowerment efforts, 4) increase the competence of KHA in policy implementers, focus on allocating the budget for implementing KLA policies and seeking alternative sources of financing.